Pengukuran Pengeluaran Energi pada Hari Kerja dan Hari Libur Menggunakan Aplikasi Smartphone pada Mahasiswa IPB - Aisyah Fathul Jannah; Dodik Briawan (Media Kesehatan Masyarakat Indonesia, 2018)
The effect of globalization made teenagers use health applications to achieve body fitness. The caloriescounter application is more practical and fast method to use. This study aimed to analyze energy expenditure inBogor Agricultural University students with smartphone application compared with estimated energy expenditureusing Physical Activity Level (PAL). The study design of this research was cross sectional study involving 61 studentsas samples. Physical activity data in a day were collected in two ways, using questionnaire and SamsungHealth application. Energy expenditure was measured during weekday and weekend. Energy expenditure measuredby Samsung Health application on weekday was 1130±719 kcal in male students and 634±195 kcal in femalestudents meanwhile on weekend was 1124±659 kcal in male students and 679±232 kcal in female students. Energyexpenditure measured by Samsung Health was smaller than energy expenditure measured by 1x24 hour physicalactivity record for both female and male students. The results can occur because not all activities can be measuredin Samsung Health. The results of energy measurements with Samsung Health still need to be estimated throughequations, especially in subjects with light intensity activities.